Design Arduino-Based Smart Laboratory - Erwinsyah Simanungkalit; Mardhiatul Husna; Jenny Sari Tarigan (Jurnal Mantik, 2021)
Electronic devices including Air Conditioner is always used during lecture process in computer laboratory. However, based on the observation, the device is often still in turn on condition even when the lecture activities have been ended. Such less efficient use leads to electricity waste which causes electricity bills to swell. This issue can be overcome by applying automation to the electronic devices in the laboratory. It is expected that by using this automation, these electronic devices are not easily damaged because the device will only turn on when needed so that it works more efficiently and electricity waste can be avoided. Current research was conducted aiming to develop an Arduino-based smart laboratory. This research was conducted in a computer laboratory at the Department of Commerce Administration, State Polytechnic of Medan. Based on the data obtained from the implementation stage, it showed that the Arduino-based Smart Laboratory System was functioning properly and can be used in computer laboratories. Keywords: Smart laboratory, Arduino, Microcontroller.